Architecture for children: Understanding children perception towards built environment - Said, Ismail (2007)
This paper discusses the importance to teach students on children’s architecture base on the perception of the children, not on the presumption of adults. It focuses on the approach teaching design and planning of built environment for young children, early to middle childhood. A trans-disciplinary approach is introduced integrating the knowledge of childhood development, architecture and landscape architecture. Therefore, teaching design studio on children’s architecture begins with the discussion on functioning of children to the built environment. That is, how sensorial and motoric actions as well as social activities of children are influenced by the elements of architecture and landscape. Finally, the effects on children’s functioning are discussed in terms of designing and planning buildings and landscape for the children.